Experimental research of drying houttuynia cordata by heat pump drying system - Truong , Huu Sang (Journal of Technical Education Science, 2019)
The study aims to determine the relationship of technical parameters for drying Houttuynia Cordata by heat pump drying system (HPD). Parameters such as drying - chamber temperature, drying - air velocity and drying - time to influence color, scent, and the content of pharmaceutical substances in dried Houttuynia Cordata. An experiment was conducted in the temperature range from 35 0C to 55 0C, drying- air velocity from 1 m/s to 1.6 m/s, The experimental processes showed that a suitable drying mode for Houttuynia Cordata was found. With an input moisture content of Houttuynia Cordata w1: 70%, the final moisture content w2: 6%: temperature chamber at 45 0C, drying-air velocity: 1.6 m/s, drying - time: 8 hours. When drying in this mode, the color of the product is green, less distorted. Flavonoid content in dried Houttuynia Cordata : 5.65%, E.Coli bacteria do not appear. Power consumption (SEC): 1.7 kWh/kg , specific moisture extraction rate (SMER): 0.96 kg/kWh, the COPHPD : 4.8. The above results showed that the HPD works stably, dryed - Houttuynia Cordata is satisfactory, and this HPD system with its drying mode can be applied to production.